Effect of thermal boundary conditions on heat transfer performance of liquid–liquid Taylor flow through a microchannel with obstruction. (6th July 2021) - Sankepally, Chandrasekhar; Patel, Akash; Vysyaraju, Raju R. K.
Abstract: Two‐phase Taylor flow through microchannels has attracted the attention of many researchers because of its enhanced heat transfer characteristics. The heat transfer rate of two‐phase flow is higher than the basic primary fluid flow through the same microchannel. This higher heat transfer rate is further improved by droplet manipulation techniques along with various thermal boundary conditions, which is the aim of the present work. In this novel work, the numerical investigation was carried out on liquid–liquid Taylor flow and heat transfer characteristics through a 2D rectangular microchannel with an obstruction in the path. The effect of capillary number, size, and position of the obstruction on heat transfer behaviour of Taylor flow was also analyzed. The height and length of the microchannel were taken as 100 and 3000 μm, respectively. Water and mineral oil were taken as working fluids. Results show that the Nusselt number of Taylor flow with obstruction increases by 76% compared to single‐phase flow and significantly increases over the Taylor flow without obstruction. Further, the study explored the effect of modulated wall temperature on Taylor flow heat transfer for optimum parameters of capillary number, size, and position of the obstruction and an improvement of 290% was achieved in heat transfer compared to that of single‐phase flows.